Pengaruh Motivasi Terhadap Produktivitas Kerja Pegawai Administrasi Keuangan Medis Rumah Sakit TNI - Al Dr. Mintohardjo - Impa Penanggu; Wahyudin Sastramenggala; Sasli Rais (Klak Klik Inovasi Digital, 2020)
This study aims to find out the influence of motivation on employee productivity in the Medical Finance Administration Department of THE NAVY Hospital Dr. Mintoharjo Jakarta. The research was conducted at the TNI Al Dr. Mintohardjo Hospital Jakarta precisely in the Medical Administration section of the TNI Al Hospital Dr. Mintohardjo Jakarta which is located at Jalan Bendungan Hilir Tanah Abang, Central Jakarta. This research was conducted from March to June 2014. The method carried out in this research is regression analysis. This is done to find out the relationship between the two variables studied, as well as to find out if one variable has a significant effect on the other variable. The results showed that Work Motivation has a significant and positive effect on Employee Work Productivity, the amount of influence is 54.31 percent. While the remaining 45.69 percent was influenced by other variables outside the research such as Discipline, Remuneration, Leadership, Work Culture, and Competence